Bronchoalveolar lavage to evaluate new pulmonary infiltrates in allogeneic hematopoietic stem cell transplant recipients: impact on antimicrobial optimization. Issue 3 (December 2019) - Vissichelli, N.C.; Miller, K.; McCarty, J.M.; Roberts, C.H.; Stevens, M.P.; De La Cruz, O.
Summary: Background: Pulmonary complications cause significant morbidity and mortality after allogeneic hematopoietic stem cell transplant (AHSCT). Bronchoscopy with targeted bronchoalveolar lavage (BAL) is often used in AHSCT patients with suspected lower respiratory tract infection (LRTI) to help guide management. Aim: To evaluate how positive BAL results change antimicrobial management of AHSCT recipients with suspected LRTI. Methods: We performed a retrospective review of BAL results from January 2014 to July 2016 for 54 AHSCT recipients. A positive BAL was determined by culture, multiplex polymerase chain reaction (PCR), Aspergillus galactomannan antigen (AGA), and cytology. Findings: BAL was positive for infectious etiologies in 63%, and antimicrobials were adjusted in 48/54 (89%) of patients. Antibacterial escalation was predicted by a positive BAL bacterial culture (OR 7.61, P =0.017). Antibiotic de-escalation was more likely with an elevated AGA (OR 3.86, P =0.035). Antiviral initiation was more likely with positive BAL multiplex PCR (OR 17.33, P =0.010). Antifungals were more likely to be escalated or changed with an elevated AGA (OR 4.33, P =0.020). The patients with a negative BAL were more likely to be started on steroids (OR 0.19, P = 0.043). Conclusions: BAL was helpful to determine the etiology of pulmonary complications and optimize antimicrobials. The addition of AGA and multiplex PCR to standard BAL significantly impacted de-escalating antibiotics and adjusting antifungals to provide adequate coverage. The association with an elevated AGA with antibacterial de-escalation highlights a new role for BAL in antimicrobial optimization.